Adapting to climate change: An international perspective: International Conference on Climate Change Adaptation (Springer-Verlag, 1996)
The conference agreed to the following definition of adaptation to climate change: Adaptation to climate change includes all adjustments in behavior or economic structure that reduce the vulnerability of society to changes in the climate system.The preparation for climate change adaptation will require more quantitative analysis, including identification, analysis, costing, and evaluation of a broad spectrum of adaptation options related to ecosystem, human health, economy, and society, as well as support for effective communication of analysis results to stakeholder groups to increase their society acceptability